Redetermination of the crystal structure of (2E,4Z,13E,15Z)-3,5,14,16-tetramethyl-2,6,13,17-tetraazatricyclo[16.4.0.07,12]docosa-1(22),2,4,7,9,11,13,15,18,20-decaene, C22H24N4 - Dey Lucky; Rabi Saswata; Begum Zinnat A.; Takase Tsugiko; Rahman Ismail M. M.; Tiekink Edward R. T.; Roy Tapashi Ghosh (Zeitschrift für Kristallographie - New Crystal Structures)
C22H24N4, triclinic, P1‾ $P‾{1}$ (no. 2), a = 9.217(4) Å, b = 9.774(4) Å, c = 10.843(4) Å, α = 96.770(2)°, β = 101.791(5)°, γ = 105.873(3)°, V = 903.9(6) Å3, Z = 2, R gt(F) = 0.0391, wR ref(F 2) = 0.1069, T = 93(2) K.